2002
DOI: 10.1034/j.1600-0455.2002.430407.x
|View full text |Cite
|
Sign up to set email alerts
|

Thymic lesions and myasthenia gravis. Diagnosis based on mediastinal imaging and pathological findings

Abstract: In MG patients CT is a sensitive, specific and efficient modality for detecting thymoma, but is less so for detecting thymic hyperplasia. MR was shown to be accurate in detecting invasive thymoma both preoperatively and in postoperative follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 23 publications
(27 reference statements)
2
21
0
Order By: Relevance
“…In spite of the technical development in CT, regarding qualitative assessment, similar accuracy data were obtained to the study of Pirronti et al 15 (86.7% versus 83%), suggesting limitations in qualitative analysis of CT. More-over, although Batra et al 14 demonstrated that MRI added no significant information to results obtained with CT, in the present study at qualitative assessment, MRI (with the addition of chemical-shift imaging) was more reliable than CT in discriminating THY from non-thymomatous condi-tions, with an overall accuracy of 96.4%. In the present cohort, most of cases in which CT failed (7/11, 64%) were TLH with a focal appearance and soft-tissue attenuation, a condition that was reported in 20% of patients with MG by Nicolau et al 8 and which is indistinguishable from THY if no obvious fat infiltration is seen.…”
Section: Qualitative Assessmentsupporting
confidence: 68%
See 1 more Smart Citation
“…In spite of the technical development in CT, regarding qualitative assessment, similar accuracy data were obtained to the study of Pirronti et al 15 (86.7% versus 83%), suggesting limitations in qualitative analysis of CT. More-over, although Batra et al 14 demonstrated that MRI added no significant information to results obtained with CT, in the present study at qualitative assessment, MRI (with the addition of chemical-shift imaging) was more reliable than CT in discriminating THY from non-thymomatous condi-tions, with an overall accuracy of 96.4%. In the present cohort, most of cases in which CT failed (7/11, 64%) were TLH with a focal appearance and soft-tissue attenuation, a condition that was reported in 20% of patients with MG by Nicolau et al 8 and which is indistinguishable from THY if no obvious fat infiltration is seen.…”
Section: Qualitative Assessmentsupporting
confidence: 68%
“…8,14,15 Furthermore, although two recent studies have demonstrated chemical-shift MRI as an effective technique for MG patients, no studies have compared the accuracy of CT and chemical-shift MRI in differentiating THY from TLH and NT by using both qualitative assessment and quantitative data. 16,17 The aim of the present study was to compare the reli-ability of CT and chemical-shift MRI in patients with gener-alised MG for distinguishing THY from TLH and NT using morphological criteria and quantitative data (radiodensity [HU] for CT, SII for chemical-shift MRI), with the proposal of optimal cut-off point values for each quantitative parameter, and to determine which technique is more accurate.…”
Section: E12mentioning
confidence: 99%
“…In a study of 104 patients with MG who underwent thymectomy, CT showed thymoma in 46 of 52 patients (sensitivity 88.5% and specificity 95%) and thymic hyperplasia in 16 of 44 (sensitivity 36% and specificity 95%) (25). A recent report suggested chemical shift MRI to be beneficial in differentiation of thymomas from thymic hyperplasia in non-MG patients (15,16).…”
Section: Thymomamentioning
confidence: 99%
“…MG is commonly associated with thymic pathologies, including lymphofollicular hyperplasia in 65%-77%, and thymoma in 15%-30% (25). It is generally agreed that thymectomy is indicated in patients affected by generalized MG between the age of puberty and 50 to 60 years.…”
Section: Thymomamentioning
confidence: 99%
“…The pathological confirmed thymoma is accurate in individual patients, but might lead to selection bias in population-based association studies due to various proportions of MG patients who are not advised by treating neurologists or decline to receive thymectomy. Although CT scan is considered as the main screening tools for thymoma, with high sensitivity and specificity, thymic hyperplasia is sometimes misdiagnosed as thymoma solely on CT imaging, while small thymoma beyond the resolution of imaging might be missed (15). MRI does not add the sensitivity in the screening of thymoma (16).…”
Section: Relative Precision In the Main Domains Of Myasthenia Gravis mentioning
confidence: 99%